Robust finite time cooperative control of second order agents:A Multi-input Multi-output higher order super-twisting based approach - Kamal S.; Sachan A.; Kumar D.K.; Singh D. (My University, 2025)
This paper studies the formation of multiple mobile agents with double integrator dynamics and their target tracking. An algorithm consisting of an observer and a feedback control law of the nonsmooth type is proposed for the purpose of achieving finite-time formation and target tracking. The development is based on the Multi-input Multi-output (MIMO) super-twisting like approach aiming at finite time convergence without chattering. In addition to the formation; tracking, chattering prevention and robustness is also provided by the sliding mode mechanism which is demonstrated by simulations. © 2018 ISA